2021
DOI: 10.1177/00307270211019758
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring rice varieties to consumer preferences induced by cultural and colonial heritage: Lessons from New Rice for Africa (NERICA) in The Gambia

Abstract: Rice breeding priorities in Africa often focus on agronomic gains. However, being a net importer of rice, the continent’s varietal replacement success also crucially hinges on new varieties’ market competitiveness vis-à-vis imports. Markets have been profoundly shaped by cultural and colonial heritage. Indigenous preferences for African rice can be traced back to ancient rice domestication and have been subsequently influenced by Asian rice import standards as a result of colonial import substitution policies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(50 reference statements)
0
13
0
1
Order By: Relevance
“…Therefore, research efforts need to be intensified to develop varieties with high yield and desirable grain quality in all other countries of SSA. With an increase in income, consumer preferences for high-quality rice are increasing and their quality preferences are different in different regions of the globe (Britwum and Demont, 2021; Calingacion et al, 2014). Therefore, there is a need for the development of more varieties with high yield potential for different regions of the globe with desirable grain quality.…”
Section: The Shape Of Rice Agriculture Towards 2050mentioning
confidence: 99%
“…Therefore, research efforts need to be intensified to develop varieties with high yield and desirable grain quality in all other countries of SSA. With an increase in income, consumer preferences for high-quality rice are increasing and their quality preferences are different in different regions of the globe (Britwum and Demont, 2021; Calingacion et al, 2014). Therefore, there is a need for the development of more varieties with high yield potential for different regions of the globe with desirable grain quality.…”
Section: The Shape Of Rice Agriculture Towards 2050mentioning
confidence: 99%
“…Successful substitution of imported with local rice requires that the quality of the latter matches consumer preferences. Consumers in coastal countries featuring major seaports and remote from cultural heritage have been found to develop preferences for the characteristics of imported Asian rice, while consumers exposed to rice cultural heritage either through geographical proximity to loci of African rice domestication or through genealogical ties to the original domesticators have been shown to preserve indigenous preferences for local rice ( Demont, 2013 ; Demont and Ndour, 2015 ; Demont et al, 2017 ; Britwum and Demont, 2021a , b ). Countries endowed with rice cultural heritage, however, were found to attract lower levels of investment in modern milling ( Soullier et al, 2020 ), presumably because demand for local rice with “authentic finish” is stronger than demand for rice with “import quality finish.” Rice imports have tended to be better milled (more whitened and polished) because the presence of the bran shortens its storability.…”
Section: Cultural Heritage Preference Matching and Food Securitymentioning
confidence: 99%
“…For example, the goal of boosting local rice production in the light of a dichotomy of consumer preferences for imported Asian and locally produced African rice spurred breeding priorities towards the development of NERICA varieties, which are hybridized to combine superior resilience and agronomic traits from the heritage African rice variety, O. glaberrima and the Asian variety, O. sativa . Analyzing results from auction experiments in secondary centers of rice domestication in the Senegambia region, Britwum and Demont (2021a , b) segmented participants based on ethnic affiliation into two groups: those with genealogical ties to original rice domesticators, and those without rice cultural heritage. The authors found that descendants from rice domesticators valued NERICAs more if the products matched the authentic finish of heritage rice, i.e., unbroken grains, while immigrants from the north and northeast without cultural heritage preferred the common “100% broken rice” grade of imports into this region.…”
Section: Cultural Heritage Preference Matching and Food Securitymentioning
confidence: 99%
See 2 more Smart Citations